DOCKING, SYNTHESIS, CHARACTERIZATION AND ANTICANCER ACTIVITY OF 4-(4'-HYDROXY, 3'-METHOXY) PHENYL, BUT-2-ONE-3-ENE, A CURCUMIN ANALOGUE PRECURSOR - M., Karpakavalli; Kumar, Preethi; A., Sanglimuthu; P., Kumar E. (International Journal of Current Pharmaceutical Research, 2016)
Objective: Curcumin, a phytoconstituent of Curcuma longa has pursued the attention of research chemists, as it is found to possess a number of pharmacological activities. Autodock is an automated procedure for predicting the interaction of ligands with biomacromolecular targets. 4-(4'-hydroxy, 3'-methoxy) phenyl, but-2-one-3-ene, a curcumin analog precursor is aimed to be synthesized and tested for anticancer activity. Methods: Autodock software utilized for the prediction of the fruitfulness of the target molecule. The aldol reaction is a powerful means of forming carbon–carbon bonds in organic chemistry. Aldol condensation of monocarbocyclic aldehyde and the enol form of a 2, 4-diketone in the presence of an organic amine catalyst, the principle is used for the synthesis of said molecule. The invention also relates to the use of the synthesized product for in vivo acute toxicity and in vitro anticancer activity. Results: The synthesized compound was characterized both by physical and spectral data. In acute toxicity study, no mortality and thereby no toxic effect from the compound (500-62.5 µg/ml). Against MCF-7, the test drug exhibited potent cytotoxicity with CTC50 values ranging from 42.0 to 89.0 when tested with drug concentrations ranging from 500-62.5 µg/ml and average CTC50 was 125 µg/ml while with Vero cell line the compound showed mild cytotoxicity. Conclusion: The experiments confirmed the fact of reliability of the synthesized compound 4-(4'-hydroxy, 3'-methoxy) phenyl, but-2-one-3-ene, a curcumin analog precursor for anti-cancer activity.